Bimbingan Keagamaan Melalui Peer Group Dalam Membentuk Perilaku Disiplin Remaja Di Panti Asuhan - Siti Alawiyah; Mu'minatul Zanah (Department of Islamic Guidance and Counseling, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2018)
This paper aims to find out religious guidance through peer group at the orphanage Griya Orphans and disadvantaged Bandung, condition behavior discipline adolescents in orphanages for orphans and disadvantaged Griya Bandung before got religious guidance, and influence religious guidance through peer group in shaping behavior discipline adolescents in orphanages Griya Orphans and disadvantaged children. Knowing the religious guidance activities through peer group at the orphanage Griya Orphans and disadvantaged Bandung, as well as the conditions of behavior discipline adolescents in orphanages for orphans and disadvantaged children before Griya got religious guidance. Research methods method using survey techniques using quantitative data types, data collection was done through observation, interview, questionnaire and the study of librarianship, data analysis was performed by means of test validity, reliability, analysis descriptive, a test of normality, the simple regression model and the product moment correlation. The results of this research show that the religious Guidance through peer group gives a positive and significant effect against Teen Discipline Behavior variables, that is, the better the Religious Guidance through Peer Group it will have an impact on improved the behavior of the discipline. Multiple regression analysis produces the model Y = 14,664 + 0.815 (X) and the coefficient of determination of 0693, meaning Religious Guidance, through peers give influence on the behavior of Teenage Discipline of 69.3%, while 30.7% is the influence of other variables that are not observed. Tulisan ini bertujuan untuk mengetahui bimbingan keagamaan melalui peer group di panti asuhan Griya Yatim dan Dhuafa Bandung, kondisi perilaku disiplin remaja di panti asuhan Griya Yatim dan Dhuafa Bandung sebelum mendapat bimbingan keagamaan, dan pengaruh bimbingan keagamaan melalui peer group dalam membentuk perilaku disiplin remaja di panti asuhan Griya Yatim dan Dhuafa Bandung. Mengetahui kegiatan bimbingan keagamaan melalui peer group di panti asuhan Griya Yatim dan Dhuafa Bandung, serta kondisi perilaku disiplin remaja di panti asuhan Griya Yatim dan Dhuafa sebelum mendapat bimbingan keagamaan. Metode penelitian menggunakan metode teknik survey dengan menggunakan jenis data kuantitatif, pengumpulan data dilakukan melalui observasi, wawancara, kuesioner dan studi kepustakaan, analisis data dilakukan dengan cara uji validitas, uji reliabilitas, analisis deskriptif, uji normalitas, model regresi sederhana dan korelasi product moment. Hasil penelitian ini menunjukkan bahwa Bimbingan Keagamaan melalui peer group memberikan pengaruh yang positif dan signifikan terhadap variabel Perilaku Disiplin Remaja, artinya semakin baik Bimbingan Keagamaan melalui Peer Group maka akan berdampak pada peningkatan Perilaku Disiplin. Analisis regresi berganda menghasilkan model Y = 14.664 + 0.815(X) dan koefisien determinasi sebesar 0.693, artinya, Bimbingan Keagamaan melalui teman sebaya memberikan pengaruh terhadap Perilaku Disiplin Remaja sebesar 69,3%, sedangkan 30,7% sisanya merupakan pengaruh dari variabel lainnya yang tidak diamati.